1982
DOI: 10.2172/6727409
|View full text |Cite
|
Sign up to set email alerts
|

Environmental control technology for shale oil wastewaters

Abstract: A03 ,051-075 A M 1076-1M) 4 A05 < 101-125 A06 i126-150 A07 , 't91-175 MY)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…13) and others at Battelle are conducting studies of steam stripping, anaerobic and aerobic biological treatment, and carbon adsorption. These studies, to date, have indicated that steam stripping is viable and that biological treatment of some waters may be feasible if powdered activated carbon is added to the reactor and if long cell residence times are used, Steam stripping of Geokinetics retort water (initial NH3 = 3,000 mg/1) removed 90 percent of the ammonia with recycle of condensate at a boiloff rate of 4.5 percent and over 99 percent of the ammonia without recycle at a boiloff rate of 5.3 percent.…”
mentioning
confidence: 99%
“…13) and others at Battelle are conducting studies of steam stripping, anaerobic and aerobic biological treatment, and carbon adsorption. These studies, to date, have indicated that steam stripping is viable and that biological treatment of some waters may be feasible if powdered activated carbon is added to the reactor and if long cell residence times are used, Steam stripping of Geokinetics retort water (initial NH3 = 3,000 mg/1) removed 90 percent of the ammonia with recycle of condensate at a boiloff rate of 4.5 percent and over 99 percent of the ammonia without recycle at a boiloff rate of 5.3 percent.…”
mentioning
confidence: 99%